KEMAMPUAN MENEMUKAN IDE POKOK PARAGRAF BERBAGAI JENIS WACANA DALAM NASKAH SOAL UN OLEH SISWA KELAS X SMA SATRIA NUSANTARA BINJAI TAHUN PELAJARAN 2012/2013 - DELI GUSMIATI (Basastra, 2013)
This study aims to describe the students’ ability to find the main ideas of paragraph in writing of UAN by the ten Grades of students’ of SMA Satria Nusantara Binjai in Academic Year 2012/2013, which amounted to 200 students and that a sample as many as 30 students. Sampling was done by determining the class to be representative of the population studied. The research method used was descriptive method which describe the phenomena of  the real situation. The test was given by the students through objective test which consists of 20 items. It consists of descriptive, narration, argumentation, persuasion, and exposition. To analyze the students’ ability to find the main idea, it was used the percentage as in the following. The findings indicate that the students’ ability of ten Grade students of Senior High School in Academic Year 2012/2013 to find the main ideas of paragraph in UAN was categorized Good, where the means score of the students’ 70,33. From the 5 kinds of writing, descriptive writing was easy to be understood by the students. It was proved from 106 or 24.82% and the persuasion writing is more difficult for the students. It was proved 60 or 14,51%. Keywords: students’ ability, main ideas, paragraph.